Answer:
A≈12.57
r Radius 2
Step-by-step explanation:
Answer:
Kimberly
Step-by-step explanation:
My mother gave me the name
Answer:
The irrational conjugate theorem states that if a polynomial equation has a root (a + √b), then we can say that the conjugate of (a + √b), i.e. (a - √b) will also be another root of the polynomial.
Step-by-step explanation:
The irrational conjugate theorem states that if a polynomial equation has a root (a + √b), then we can say that the conjugate of (a + √b), i.e. (a - √b) will also be another root of the polynomial.
For example, if we consider a quadratic equation x² + 6x + 1 = 0, then two of its roots are - 3 + √8 and - 3 - √8 and they are conjugate of each other. (Answer)
Answer:
y = (x-3)^2 - 17
Step-by-step explanation:
To complete the square, take the middle term bx and divide it in two. Then take the square.
x^2 - 6x - 8 has bx = -6x. Take -6/2 = -3. Square -3^2 = 9.
Now to finish completing the square add 9 and subtract 9 from one side.
y = x^2 - 6x - 8
y = (x^2 - 6x +9) -9 - 8
y = (x-3)^2 - 17
First you must know that for remarkable angles: cos (0) = 1, cos (π) = - 1, cos (π / 2) = 0, cos (3π / 2) = 0, cos (2π) = 1. Then, by simple substitution in the given formula, you can find the solutions of x. Which for the interval [0, 2π) are: x = π, x = pi divided by two and x = three pi divided by two.Attached solution.